Uncovering the Richness of Local Culture: Utilizing Traditional Wisdom for Teaching Indonesian Language and Literature in the Vuca Era - Septiari, Wahyu Dini; Muryati, Sri; Pardyatmoko (Proceedings Series on Social Sciences & Humanities, 2024)
The VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era presents its own challenges in teaching Indonesian language and literature. The utilization of local wisdom is a potential solution to enrich the learning process. This study aims to explore how to integrate local wisdom in teaching Indonesian language and literature in the VUCA era. The research method used is descriptive qualitative. Data were collected through in-depth interviews with experts in the field of Indonesian language and literature, as well as observation of teaching practices in several educational institutions. The data were analyzed thematically to identify patterns and trends in the use of local wisdom in teaching. The results show that there are various potentials of local wisdom that can be integrated in teaching Indonesian language and literature, such as the exploration of folklore, proverbs, and traditional cultural values. This integration can be done through the development of local wisdom-based teaching materials, the transformation of local wisdom-based literary works, as well as the development of local linguistics and innovation in learning Indonesian language and literature in the VUCA era. This study concludes that the utilization of local wisdom in teaching Indonesian language and literature in the VUCA era can strengthen cultural identity, increase the relevance of learning, and encourage students' creativity and critical thinking skills. This research is expected to provide insights for educational practitioners in developing Indonesian language and literature learning that is responsive to the challenges of the VUCA era.